MODIFICATION OF LINDUR STARCH (Bruguiera Gymnorrhiza L.) BY OXIDATION USING SODIUM HYPOCLORITE AND FERRO SULPHATE CATALYST - Lucia Hermawati Rahayu; Sri Sutanti; Mumpuni Asih Pratiwi; Rahelia Cahyaningtyas (Journal of Chemical Process and Material Technology, 2022)
Lindur fruit (Bruguiera gymnorrhiza L.) is widely available in Indonesia and has a high carbohydrate content, so it has the potential to be developed as a new source of energy and starch. So far, the use of lindur fruit is still limited to substitute rice and snacks. Therefore, it is necessary to make efforts to increase the utilization of lindur fruit by processing it into lindur starch and its derivatives (modified starch). The properties of lindur starch need to be improved in order to have wider uses in the food and non-food industries. The purpose of this study was to modify lindur starch by oxidation using NaOCl with ferrous sulfate as a catalyst. In this study, the effect of sodium hypochlorite concentration (2%, 4%, 6%, and 8%) and ferrous sulfate concentration (0%, 0.1%, 0.2%, and 0.3%) on the physicochemical characteristics of starch was studied. the resulting oxidized leachate and determined the optimal conditions. The results showed that all the variables studied affected the oxidation reaction of lindur starch. Oxidation at 4% NaOCl concentration and 0.2% ferrous sulfate concentration was able to produce the best values for carboxyl content, solubility, and swelling.